Humanistic Model in the Development of Islamic Religious Education Curriculum - Azmi, Mohamad (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2022)
The humanistic model of Islamic religious education aims to develop the human aspects and values of life within the context of religious learning. In this approach, the focus is placed on understanding, internalizing, and applying the teachings of Islam in everyday life, with the goal of shaping positive attitudes, character, and morality in students. In the humanistic model, students take center stage in the learning process, actively engaging and encouraged to develop their emotional, social, and spiritual aspects. The instructional methods employed include discussions, reflections, simulations, role-playing, and relevant real-life experiences. The main objective is to cultivate morally upright Muslim individuals who possess empathy, tolerance, social concern, and awareness of the needs of others.